2007
DOI: 10.1038/sj.bmt.1705864
|View full text |Cite
|
Sign up to set email alerts
|

The impact of histologic grade on the outcome of high-dose therapy and autologous stem cell transplantation for follicular lymphoma

Abstract: The impact of the follicular lymphoma (FL) histologic grade on outcomes after high-dose therapy (HDT) and autologous stem cell transplantation (ASCT) is unknown. We evaluated 219 consecutive patients with grades 1-3 FL who underwent HDT and ASCT at our center. Overall survival (OS), progression-free survival (PFS), relapse and non-relapse mortality (NRM) was estimated for each grade after controlling for other predictive factors. The number of patients with grades 1, 2 and 3 FL was 106 (48%), 75 (34%) and 38 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…Investigators in Seattle reported no differences in the outcome of ASCT on the basis of the grade of FL in more than 200 patients. 35 Similar results are available from City of Hope in a smaller series of 55 FL patients. 37 In contrast, the Nebraska group reported inferior survival, risk of progression (hazard ratio [HR], 2.14), and treatment failure (HR, 1.97) in patients with FL3 (when compared with other grades of FL) in another series of more than 200 patients.…”
Section: Sct In the Relapsed Or Refractory Settingsupporting
confidence: 71%
See 1 more Smart Citation
“…Investigators in Seattle reported no differences in the outcome of ASCT on the basis of the grade of FL in more than 200 patients. 35 Similar results are available from City of Hope in a smaller series of 55 FL patients. 37 In contrast, the Nebraska group reported inferior survival, risk of progression (hazard ratio [HR], 2.14), and treatment failure (HR, 1.97) in patients with FL3 (when compared with other grades of FL) in another series of more than 200 patients.…”
Section: Sct In the Relapsed Or Refractory Settingsupporting
confidence: 71%
“…[32][33][34] Comparative data regarding the grade of FL or the outcome of other subtypes of iNHL with SCT are limited. 35,36 Older reviews have reported conflicting reviews, with 2 of 3 relevant series reporting results from the pre-rituximab era. Prior allograft series did not routinely distinguish the grade of FL.…”
Section: Sct In the Relapsed Or Refractory Settingmentioning
confidence: 99%
“…The frequent inclusion of grade 3 FL with the more indolent or aggressive lymphomas undergoing auto- 13 , 14 or allo-HCT 15 has meant that the relative benefits of these two transplantation modalities in this unique subset of FL remains unknown. In the pre-rituximab era, Pham et al 13 observed no significant impact of grade 3 histology on survival outcomes of FL patients (grade 3, n=38, 17% of the whole cohort) after auto-HCT. In contrast, Vose et al 14 found grade 3 histology to be associated with increased risk of treatment failure (RR 1.97, p=0.004), progression (RR 2.14, p=0.006) and worse survival outcomes after auto-HCT.…”
Section: Discussionmentioning
confidence: 99%
“…While both autologous (auto-) and allogeneic hematopoietic cell transplantation (allo-HCT) can provide disease control in relapse/refractory FL 11 , 12 , no study to our knowledge, has assessed the relative efficacy of these two transplantation modalities specifically in grade 3 FL patients. Outcome studies from the pre rituximab-era that lumped grade 3 FL patients with either more indolent grade 1-2 histologies 13 , 14 , or along with more aggressive DLBCL 15 suggest that post HCT outcomes of grade 3 patients are distinct from both indolent and aggressive B-cell lymphoproliferative disorders. These observations underscore the need for specifically reappraising the role of auto- and allo-HCT in relapse/refractory grade 3 FL, in the era of chemoimmunotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…A Seattle group indicated no effect of having a higher grade (grade 3 vs. grades 1-2) of FL at auto-SCT, whereas a Nebraska group showed inferior outcomes of patients with grade 3 FL. 21,26 In the pre-rituximab era, EBMT reported the outcomes of 12 Four-fifths of the patients received auto-SCT in a disease status other than CR1. The 10-year PFS and OS for patients who were not in CR1 at auto-SCT were 28% and 48%, respectively.…”
Section: Salvage Setting For Relapsed Diseasementioning
confidence: 99%